Utilizing Rewards to Increase Learning Motivation Among Students at SMPN 10 Gresik - Kuncoro, Moch. Khudori Mainz; Jati, Sigit Pramono; Nikmah, Lailatun (ICONELT, 2024)
This research aimed to examine the effect of applying a reward system in enhancing students learning motivation at SMPN 10 Gresik and determine how they perceive it. The study was conducted using qualitative research with a case-study design. 10 students in Grade VIII were interviewed, and 3 learning processes with the reward system implemented were observed. The analysis of the data was based on qualitative techniques where themes reflecting background and motivational factors were illustrated. The results indicate that the reward system helped in motivating the students towards learning. Among the themes that emerged were confidence, a desire to engage in class activities, and improved social relationships between students. Several students reported that the rewards enhanced their learning by making it a little more fun. The prizes succeeded in raising the learning motivation of their students at SMPN 10 Gresik. The results show that creative and innovative teaching strategies are needed to involve students in the learning process.